2018
DOI: 10.1002/oby.22098
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Controlled Trial Examining the Ripple Effect of a Nationally Available Weight Management Program on Untreated Spouses

Abstract: ObjectiveFor married couples, when one spouse participates in weight loss treatment, the untreated spouse can also experience weight loss. This study examined this ripple effect in a nationally available weight management program.MethodsOne hundred thirty dyads were randomized to Weight Watchers (WW; n = 65) or to a self‐guided control group (SG; n = 65) and assessed at 0, 3, and 6 months. Inclusion criteria were age ≥ 25 years, BMI 27 to 40 kg/m2 (≥ 25 kg/m2 for untreated spouses), and no weight loss contrain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 22 publications
(40 reference statements)
2
20
1
Order By: Relevance
“…Some review studies have found that individuals tend to exhibit concordance with their family members and friends in terms of health behaviors (10) and weight (11). A small but growing number of studies have also suggested that if individuals change their exercise or diet habits, family members might also adopt these new health behaviors (12)(13)(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…Some review studies have found that individuals tend to exhibit concordance with their family members and friends in terms of health behaviors (10) and weight (11). A small but growing number of studies have also suggested that if individuals change their exercise or diet habits, family members might also adopt these new health behaviors (12)(13)(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…Weight change among the partners was not assessed in the current study. However, other researchers have noted the high correspondence in weight loss between partners and participants, suggesting that support partners losing weight promotes weight loss in participants (and vice versa) (7,(46)(47)(48). It is also possible that support partners did not know how best to support participants as they were only given general guidance and no additional training or feedback during the course of the programme, thus diminishing the potential impact of their role as a support partner (49).…”
Section: Discussionmentioning
confidence: 98%
“…This benefit was achieved without any additional cost to treatment providers. (Gorin et al 2008(Gorin et al , 1683 A number of related studies (Golan et al 2010;Schierberl Scherr, McClure Brenchley, and Gorin 2013;Cornelius, Gettens, and Gorin 2016;Gorin et al 2017Gorin et al , 2018 have found further evidence of this "ripple effect" whereby treating one spouse yields a significant outcome for the untreated spouse. For example, Golan et al (2010) find that at a six-month follow-up after treatment, spouses whose partners were treated lost significantly more weight than spouses whose partner was not treated.…”
Section: Dyadic Approaches To Obesitymentioning
confidence: 99%